YORMUHAMMAD YORI'S BENCH AND A GHAZALI COMMENTARY - Muhammadrizo Djurayev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article deals with the work of Yori Khogandi, whose works played an important role in the literary life of Kokand, but whose works have not been studied, and his state, the content and formative manifestations of the poems included in it. The article also describes considerations regarding what the elements that determine the Yori skill consist of. The process focuses on the elements that define the poet's skill, and the importance of studying his work perfectly is demonstrated.